The COVID-19 Pandemic’s Effect on the Rate of Patients in Custody Admitted for Psychiatric Evaluation at a Large Inner-City Community Health Center - Figueroa, Keishla; Bidkhanian, Patrick; Segal, Yarden; Brown, Lauren; Silva, Briana M.; Garrels, Eric; Bashir, Saif; Salehi, Mona; Alzamani, Meena; Singh, Victoria; Nafeh, Omar; Kamal, Sana; et al. (British Journal of Healthcare and Medical Research, 2025)
The COVID19 pandemic affected arguably every facet of our global society, from mental health and healthcare service utilization to economic stability and the function of our criminal justice system. Individuals within the carceral system are amongst the most vulnerable and underserved populations of the United States, facing extremely high rates of severe psychiatric illness, substance use, and distrust of the medical establishment. The pandemic exacerbated these preexisting health disparities, and previous research has shown an overall increase in rates of depression, anxiety, acute psychosis, and substance use during COVID19. This retrospective, longitudinal study investigates psychiatric emergencies amongst the arrested and incarcerated populations of the South Bronx, New York, a critically underserved region of the United States with persistently high rates of violence and arrests. Our results show an increase in rates of suicidal ideation, suicide attempts, and self-injurious behaviors, despite a significant decrease in rates of depression consultations. This study is the first of its kind; it provides a nuanced perspective on a research population often underrepresented in the literature and opens the door for areas of future research.